Drug-related side effects and adverse reactions in the treatment of migraine: a bibliometric and visual analysis - Wei, Shijie; Lv, Hao; Yang, Dianhui; Zhang, Lili; Li, Xuhao; Ning, Yike; Tang, Yu; Wu, Xinyu; Han, Jing (Frontiers in Neurology, 2024)
Background. Migraine imposes a substantial global burden, impacting patients and society. Pharmacotherapy, as a primary treatment, entails specific adverse reactions. Emphasizing these reactions is pivotal for improving treatment strategies and enhancing patients' well-being. Thus, we conducted a comprehensive bibliometric and visual analysis of relevant literature. Methodology. We conducted a comprehensive search on the Science Citation Index Expanded within the Web of Science, restricting the literature for analysis based on criteria such as document type, publication date, and language. Subsequently, we utilized various analytical tools, including VOSviewer, Scimago Graphica, the R package 'bibliometrix', CiteSpace, and Excel programs, for a meticulous examination and systematic organization of data concerning journals, authors, countries/regions, institutions, keywords, and references. Results. By August 31, 2023, the literature was distributed across 379 journals worldwide, authored by 4235 individuals from 1726 institutions. It featured 2363 keywords and 38412 references. 'HEADACHE' led in publication count, with 'SILBERSTEIN S' as the most prolific author. The United States ranked highest in publication volume, with 'UNIV COPENHAGEN' leading among institutions. Conclusions. Our research findings indicate that researchers in the field continue to maintain a focus on the calcitonin gene-related peptide (CGRP) system and explore diverse mechanisms for drug development through the application of novel biotechnological approaches. Furthermore, it is imperative to enhance the assessment of clinical trial outcomes, consistently monitor the efficacy and safety of prominent drugs such as Erenumab and Fremanezumab. There is a need for further evaluation of acute and preventive treatments tailored to different populations and varying types of migraine.